Potential Role of Drebrin A, an F-Actin Binding Protein, in Reactive Synaptic Plasticity after Pilocarpine-Induced Seizures: Functional Implications in Epilepsy - Lotfi Ferhat (International Journal of Cell Biology)
Several neurological disorders characterized by cognitive deficits, including Alzheimer's disease, down syndrome, and epilepsy exhibit abnormal spine density and/or morphology. Actin-based cytoskeleton network dynamics is critical for the regulation of spine morphology and synaptic function. In this paper, I consider the functions of drebrin A in cell shaping, spine plasticity, and synaptic function. Developmentally regulated brain protein (drebrin A) is one of the most abundant neuron-specific binding proteins of F-actin and its expression is increased in parallel with synapse formation. Drebrin A is particularly concentrated in dendritic spines receiving excitatory inputs. Our recent findings point to a critical role of DA in dendritic spine structural integrity and stabilization, likely via regulation of actin cytoskeleton dynamics, and glutamatergic synaptic function that underlies the development of spontaneous recurrent seizures in pilocarpine-treated animals. Further research into this area may provide useful insights into the pathology of status epilepticus and epileptogenic mechanisms and ultimately may provide the basis for future treatment options.